1997
DOI: 10.1542/peds.99.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Open Lung Biopsy in Children

Abstract: The morbidity and mortality rates of children with ARF undergoing OLB for diffuse pulmonary infiltrates differ considerably from those of children without ARF. For children with ARF, OLB is associated with the risk of prolonged ventilatory support, recurrent pneumothoraces, and air leaks. These complications may be attributable to such patients' having diseased lungs with poor healing. Moreover, these complications may, in turn, contribute to the patients' poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
3
25
2
1
Order By: Relevance
“…OLB has been the primary surgical approach in young children (120,121,132,133). However, VATS visualizes a greater percentage of the lung and permits the sampling of different lobes with the same incision sites (a consensus statement recommends multiple biopsy sites [134], even though there are limited data to support this approach [58]).…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…OLB has been the primary surgical approach in young children (120,121,132,133). However, VATS visualizes a greater percentage of the lung and permits the sampling of different lobes with the same incision sites (a consensus statement recommends multiple biopsy sites [134], even though there are limited data to support this approach [58]).…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Studies on SLB in children are scarce, all are retrospective, and they describe small cohorts which are mostly heterogeneous [5,11,12,13,14,15,16,17,18,19,20,21,22]. This makes drawing conclusions about the role of this procedure in the management of immunocompromised patients presenting with pulmonary findings a difficult task.…”
Section: Discussionmentioning
confidence: 99%
“…In many of the publications, the study population is heterogeneous and consists of primary immune deficiencies, SCT and patients on different chemotherapy regimens. The severity of the clinical condition of patients in these studies also varies considerably; the proportion of patients who were ventilated with or without multiorgan failure in critical-care units, when the SLB was performed, ranged from 2 to 100% [12,13,14,15,16,17,18,19,23]. Our study demonstrated a lower yield of SLB in comparison to the results presented by others, with the estimation of the yield of SLB ranging from 33 to 69% across studies [5,13,14,15,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations